In Vivo Anti-Thyroid Evaluation and In Silico Profiling of Essential Oils from Medicinal Plants: Extraction, GC/MS Characterization, ADMET Prediction, DFT Calculations, Molecular Docking, and Dynamics Simulation. - Meziou Mabrouka; Meziou Mabrouka; Meziou Mabrouka (Université d'EL-Oued., 2025)
Hypothyroidism is a medical condition characterized by decreased production of thyroid hormones, namely thyroxine (T4) and triiodothyronine (T3). These hormones play an important role in regulating the body's metabolism, growth, and development. Hypothyroidism is linked to the ineffectiveness of the molecules used in its treatment. This has prompted the World Health Organization to promote the use of traditional medicine as an alternative solution. This study aimed to evaluate the therapeutic effect of essential oils extracted from Ammodaucus leucotrichus and Mentha piperita in the treatment of hypothyroidism, using in vivo experiments on a rat model experimentally induced by benzylsuracil, combined with GC/MS chemical analysis and in silico simulation. The chemical results showed that Ammodaucus leucotrichus oil mainly contained sabinene (32.03%), β-pinene (10.77%) and 1,4-p-menthadiene (14.14%), while Mentha piperita oil was characterized by the presence of menthol (38.19%), menthone (21.65%) and 1,8-cineole (12.47%). The groups treated with perilla oil showed significant improvements in hormonal parameters: T3 (1.92 ± 0.03 ng/mL), T4 (6.13 ± 0.12 µg/dL), with a decrease in TSH (0.41 ± 0.02 µIU/mL). Peppermint oil also showed improvements in T3 (1.81 ± 0.05 ng/mL), T4 (5.79 ± 0.13 µg/dL), and TSH (0.53 ± 0.03 µIU/mL). In silico results also demonstrated the ability of the active compounds to effectively bind to the TPO enzyme, with perilla aldehyde recording a binding energy of -6.9 kcal/mol. These results confirm the potential of these oils as supportive natural therapeutic models for hypothyroidism, with a mechanism combining hormonal adjustment and enzyme inhibition, supporting the development of alternative herbal supplements or medicines to conventional treatment.
Toxicology
Keywords: Mentha piperita; Ammudaucus leucotrichus; swissadme; benzylthiouracil; Hypothyroidism; rats; essential oil.